Occult HBV infection in Chinese blood donors: role of N-glycosylation mutations and amino acid substitutions in S protein transmembrane domains - Zhang, Lu; Chang, Le; Laperche, Syria; Ji, Huimin; Zhao, Junpeng; Jiang, Xinyi; Wang, Lunan; Candotti, Daniel (Emerging microbes & infections, 2019)
Occult hepatitis B virus infection (OBI) is a low-level asymptomatic phase of HBV infection. Evidence of OBI clinical relevance is emerging but the mechanisms of its occurrence remain unclear. In this study, the molecular characteristics of 97 confirmed OBI from Chinese blood donors were analyzed and relevant mutations were identified. Recombinant HBsAg bearing these mutations were expressed in vitro and the antigenicity and HBsAg secretion properties were analyzed. Results showed that 45 (46.4%) genotype B, 50 (51.5%) genotype C, and 2 (2.1%) genotype D sequences were identified. Two groups of mutations in the S gene were significantly associated with OBI. The first group included mutations creating new N-linked glycosylation sites at positions s116, s123, s130, and s131 + s133 or removing the existing one at s146. Mutations TCT123-125NCT/NFT were associated with reduced antigenicity, while TST116-118NST, GTS130-132NTS, and TSM131-133NSS/NYT/NST were associated with varying levels of impaired HBsAg secretion. N146 mutations had no effect on HBsAg production pattern. The second group included substitutions within the S transmembrane domains TMD1-3. Only mutations C85R, L87R, L88R, and C90R within TMD2 were associated with defective HBsAg production. These mutations appear to be rare and mostly strain specific but they may contribute to the multifactorial occurrence of OBI.